THE ROLE OF BIOREOLOGY IN ENCANCING DRUG DELIVERY SYSTEMS (The New Uzbekistan Journal of Medicine, 2025)
The investigation of the movement and alteration of biological fluids and tissues, known as bioreology, is crucial in the development of drug delivery mechanisms. Researchers can create therapeutic carriers that are tailored for efficient transportation, absorption, and release within the body's intricate biological surroundings by scrutinizing important rheological properties like viscosity, shear stress, and viscoelasticity. This article investigates the impact of biomechanical principles on the efficiency of contemporary drug delivery systems, specifically in cancer treatment, heart conditions, and brain disorders. Furthermore, it brings attention to obstacles like individual patient differences and talks about upcoming trends like personalized medicine and stimuli-responsive materials. The combination of bioreology with cutting-edge technologies offers the potential to transform precise and effective drug administration, enhancing patient results and facilitating new healthcare advancements.